Italian translation and validation of the Nordic Occupational Skin Questionnaire (NOSQ-2002) - Chiesi, Andrea; Pellacani, Giovanni; Di Rico, Renato; Farnetani, Francesca; Giusti, Giulia; Pepe, Patrizia; Prampolini, Paola; Gobba, Fabrizio Maria (La Medicina del Lavoro, 2016)
Background: Because of their frequent occurrence, in various situations it may be appropriate to carry out screening of skin disorders in groups of workers. For this purpose the self-administered standardized questionnaires are of great use. Among the best known is the Nordic Occupational Skin Questionnaire (NOSQ-2002), which had not yet been translated and validated in Italian. Objectives: The aim of the study was to translate the NOSQ-2002 into Italian and validate the resulting Italian version. Methods: The original English text of the NOSQ-2002 was subjected to the ISPOR task force’s procedures for translation and cultural validation of questionnaires in health care. Subsequently, the Italian version was tested on a sample of 52 individuals to assess comprehensibility and reliability through analysis of internal consistency and stability over time and the predictive value of the clinical history through assessment of sensitivity and specificity in 32 subjects. Results: The Italian version of the NOSQ produced proved very true to the original, needing only minor changes. From interviews on the comprehensibility of the questionnaire no significant difficulties in understanding the text were detected. The results of the evaluation of internal consistency (Cronbach’s Alpha: 0.88 and 0.97) and stability (K Cohen> 0.81 in 52/57 items) indicated that the Italian version of the NOSQ may be considered reliable for the purposes proposed. There were also excellent sensitivity and specificity results, which were 86% and 89% respectively. Conclusions: The Italian version of the NOSQ presented here is appropriate for self-administration and is reliable for use in studies on skin diseases in groups of workers.